Response of a proton exchange membrane fuel cell to step changes in mass flow rates - Kupeli, Seda; Celik, Erman; Karagoz, Irfan (Wiley-V C H Verlag Gmbh, 2021)
Transient regime effects are particularly important in fuel cells designed for vehicles. Three-dimensional modeling of a proton exchange membrane fuel cell with a serpentine channel is presented, and the response of the fuel cell to a step-change in the mass flow rates is analyzed by using the computational fluid dynamics techniques. After a validation study of the mathematical and numerical model, step increases of 20% in mass flow rates are applied to the inlet boundary conditions, and time dependent power and current density responses of the fuel cell are analyzed. Polarization curves are generated for the assessment of the fuel cell performance, and their variations in time are presented. The results show that current and power densities increase with time at low cell voltage values due to concentration losses; however, increases in power and current are negligible at high voltages.
Keywords: computational fluid dynamics; fuel cell; modeling; proton exchange membrane; step response; time constant